Colombia : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Colombia. (IMF Staff Country Reports; Country Report ;, 2009)
Colombia's economy has performed well in recent years. This 2008 Article IV Consultation highlights that economic growth in 2006-07 exceeded the regional average by a substantial margin. The authorities have acted swiftly to bolster confidence and ensure that the private sector retains access to credit. Executive Directors have commended the Colombian authorities for implementing sound macroeconomic policies and wide-ranging structural reforms, which had contributed to rapid growth and reduced vulnerabilities. Directors have also encouraged the authorities to move forward with their structural reform agenda.